Improving the patient experience through a commit to sit service excellence initiative - Cari Lidgett (The Beryl Institute, 2016)
Effective communication between nurses and patients positively impacts patient care, outcomes, and the patient experience.While in the hospital, patients receive information from multiple caregivers and are often overwhelmed and confused. Nurses make up the majority of interactions with patients and are in an ideal position to improve the patient experience from the front lines. The purpose of implementing the Commit to Sit service excellence initiative was to positively impact the patient's perception of nurse communication by nurses sitting with their patients during each shift. Outcomes were measured by the overall nurse communication composite on the Press Ganey survey, as well as the composite components of treating patients with courtesy and respect, listening carefully, and explaining understandably. Patients perceive caregivers as spending more time at the bedside when sitting versus standing. Experience Framework This article is associated with the Culture & Leadership lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Culture%20%26%20Leadership%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D" target="_blank">Access other PXJ articles related to this lens. Access other resources related to this lens